Fiscal Operations and Macroeconomic Growth: The Nigerian Experience - Idris, Miftahu; Bakar, Rosni (International Journal of Social and Administrative Sciences, 2017)
Over the years in Nigeria, the trend of fiscal expenditures continues to increase rapidly without any corresponding increase in the level of revenue. This scenario had deteriorated the fiscal stability resulting in high rate of deficits and domestic debt, as well as inducing more inflationary pressure within the market-oriented economy. In view of the decreasing price of crude oil in the international market accompanied by lower revenue generation, the rising inflationary pressure has continued to serve as a major obstacle to ensuring sustainable growth in Nigeria. With the monetary policy being constrained in addressing this problem as a result of the prevailing exchange rate regimes which adversely affect the activities of the commercial banks, this gave fiscal policy the opportunity to carry the main task of macroeconomic stabilization in Nigeria. It is in view of this background that this paper is aimed at evaluating the effects of fiscal operations on macroeconomic growth in Nigeria. Enormous literature related to fiscal operations in both developed and developing countries are reviewed, and the trends of fiscal variables are also presented. The paper adopted a descriptive method and utilized both charts and table to show the trend of fiscal elements with the aim of determining the relationship among the variables. The paper concludes that fiscal operation is ineffective in providing the needed macroeconomic environment for sustainable growth. Therefore, there is need for government to reduce the size of its deficits, broaden the revenue base by increasing the contribution from non-oil sources, and synchronize both monetary and fiscal policies in order to ensure growth and maintained stability in the economy. Also, an effectively implemented fiscal policy programs could play a vital role in overcoming these instabilities on the economy by providing a suitable framework for a more stable and predictable budget. Nevertheless, mere quantitative implementation of fiscal programs will not change the impacts of these instabilities on the economy unless viable pro-active measures are taken to fight corruption and to strengthen transparency and accountability of fiscal management in the public sector.